Approaches and Components of Health Workforce Planning Models: A Systematic Review - Somaieh Bosak; Shahram Yazdani; Mohammad Hossein Ayati (Iranian Journal of Medical Sciences, 2023)
Background: To date, there is still no uniformity in forecasting models for health workforce planning (HWFP). Different countries use various HWFP models, some of which are context-specific. The objective of this systematic review is to determine approaches and components of HWFP models.Methods: A systematic review of studies published in English and Persian between 2004 and 2021 was performed by searching PubMed Central, MEDLINE, Web of Science, Scopus, Eric, and Elmnet databases. Articles that assessed HWFP models, focused on health service delivery, used input-output models, and a clear formulation process were included. Articles that scored ≥20 points on the “strengthening the reporting of observational studies in epidemiology” checklist were considered of acceptable quality for inclusion.Results: Twenty articles were included for qualitative synthesis based on the inclusion and exclusion criteria. Most studies used the mixed method approach “supply and demand”, whereas target- and needs-based approaches were used less frequently. The number of components used to estimate supply, demand, needs, and targets were 42, 32, 11, and 6, respectively. In addition, several unique factors used in the various HWFP models were identified.Conclusion: Different approaches are used in HWFP models, which is indicative of the lack of consensus on this topic. High diversity in the identified factors is related to the approach used and the context in which the model is applied.